PENGARUH PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) TERHADAP PENINGKATAN PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK DI SEKOLAH DASAR - Marlina, Ina; Fuziawati, Linda (STKIP Subang, 2021)
This research is motivated by the lack of understanding of students' mathematical concepts in mathematics which is caused by a lack of motivation to learn in students and the lack of material connection with everyday life. Mathematics learning really needs to be learned by students because Mathematics has an important purpose to meet practical needs related to the development of students' abilities to use mathematics in everyday life, such as counting which is often experienced by students and can develop the ability to calculate weight. and content. Although Mathematics is considered important to learn, not a few students feel that Mathematics is difficult to master, so it is considered boring and makes students' interest in learning in Mathematics considered low. Based on the PISA annual study survey, the Indonesian Mathematics competency has decreased from 386 points in 2015 to 379 points in 2018 with an OECD average of 489. The benefits of studying Mathematics are used to make transactions in trade. One way to make mathematics more understandable is to use the Realistic Mathematics Education (RME) approach so that students can learn more realistically. The purpose of this study was to determine the increase in students' understanding of mathematical concepts using the Realistic Mathematics Education (RME) approach and whether there were changes that occurred after the treatment using this approach. This research was conducted with quantitative research methods and the research design of One Groups Pretest-Posttest Design. The subject of this research is class IV with a total of 28 students at SDN Curugrendeng II. The instrument used is a written test with a total of 10 questions. Calculation of data processing using Microsoft Office Excel 2007 and using IBM SPSS Statistics 22 with a significance level of 0.05. The results of this study indicate that there is an increase in students' understanding of mathematical concepts with an average value of 0.691 which is included in the medium category. Thus, the understanding of mathematical concepts of students using the Realistic Mathematics Education (RME) approach changes from before the action to the final score after the action. done. And there is an effect of the Realistic Mathematics Education (RME) approach on students' understanding of mathematical concepts by showing the results of sig.(2-tailed) 0.000 <0.05, which means H_1 is accepted so that this Realistic Mathematics Education (RME) approach can be applied to learning Mathematics in Primary school.